Migration and Equality: Should Citizenship Levy Be a Tax or a Fine? - Dumitru, Speranta (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2012)
It is often argued that development aid can and should compensate the restrictions on migration. Such compensation, Shachar has recently argued, should be levied as a tax on citizenship to further the global equality of opportunity. Since citizenship is essentially a ‘birthright lottery’, that is, a way of legalizing privileges obtained by birth, it would be fair to compensate the resulting gap in opportunities available to children born in rich versus poor countries by a ‘birthright privilege levy’. This article sets out a defence of three theses. The first states that equality of opportunity is incompatible with, and cannot be achieved in, segregated territories. The second posits that to believe that material equality compensates the injustice of restrictions on movement is to commit a ‘sedentarist mistake’. The third affirms that any citizenship levy, including the egalitarian and non-sedentarist formula I’m proposing, would be better understood as a penalty rather than a tax.